2012
DOI: 10.1126/science.1208929
|View full text |Cite
|
Sign up to set email alerts
|

Marine Microbes See a Sea of Gradients

Abstract: Marine bacteria influence Earth's environmental dynamics in fundamental ways by controlling the biogeochemistry and productivity of the oceans. These large-scale consequences result from the combined effect of countless interactions occurring at the level of the individual cells. At these small scales, the ocean is surprisingly heterogeneous, and microbes experience an environment of pervasive and dynamic chemical and physical gradients. Many species actively exploit this heterogeneity, while others rely on gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
557
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 543 publications
(567 citation statements)
references
References 51 publications
9
557
0
1
Order By: Relevance
“…This observation provides evidence for niche partitioning in the use of DOCp by bacterioplankton. Temporal fluctuations in biotic and abiotic factors, as well as microscale processes, provide a variety of substrate quantity and quality, creating numerous heterogeneous habitats that maintain the high diversity of heterotrophic bacteria in the sea (Stocker, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This observation provides evidence for niche partitioning in the use of DOCp by bacterioplankton. Temporal fluctuations in biotic and abiotic factors, as well as microscale processes, provide a variety of substrate quantity and quality, creating numerous heterogeneous habitats that maintain the high diversity of heterotrophic bacteria in the sea (Stocker, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Typical laboratory cultivation differs from the conditions microorganisms experience in their natural environments, where spatial heterogeneity is pervasive (Stocker, 2012). The lack of spatial or temporal structure in typical laboratory cultivation causes resources to be a global commodity shared by the entire experimental population.…”
Section: When Is Efficient Growth Favored?mentioning
confidence: 99%
“…Eight cellular functions have been described as the components of maintenance energy (van Bodegom, 2007) and oligotrophs have been shown to minimize costs associated with three of these functionsprotection from oxygen stress, cell motility, and the synthesis and turnover of macromolecules. A large clade of marine oligotrophs have lost the capacity to synthesize oxygen stress protectants when they are freely available in their environment (Morris et al, 2012) and many described oligotrophs are also non-motile (Lauro et al, 2009;Stocker, 2012). Additionally, genome streamlining is common in oligotrophs (Giovannoni et al, 2014), which may be an adaptation to decrease the amount of resources invested in macromolecule synthesis and turnover.…”
Section: Life History and Growth Efficiencymentioning
confidence: 99%
“…Such variation is best understood at the scale of meters, for example, over depth gradients of light or over regional (kilometer) gradients in nutrient availability. Microbial communities are also structured over much smaller spatial scales, notably the micron-scale distances separating free-living (FL) cells from those on the surfaces or within the diffusive boundary layer of suspended or sinking organic particles (Stocker, 2012). Extensive research has identified consistent taxonomic compositional differences between FL and particleassociated (PA) bacterial and archaeal communities (DeLong et al, 1993;Hollibaugh et al, 2000;Ganesh et al, 2014), as well as differences in total microbial abundance, production and enzyme activity (Simon et al, 2002;Grossart et al, 2003Grossart et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%